Reconciling Structural and Personal Expressions of Justice in Jesuit Education. Issue 1 (1st January 2020) - Sokol, Bryan W.; Sweetman, Leah; Wassel, Bobby; Franco, Christopher; Huffman, Tim
Abstract: Justice education in the Catholic, Jesuit tradition is filled with tensions, many of which surface in different community service contexts. Saint Louis University offers an institutional illustration of these tensions, both in the conceptual origins of justice education and in the practical ways that students make meaning from service experiences. The overall work of the University's Center for Service and Community Engagement is one of the practical offshoots of the Jesuit mission to simultaneously promote faith and justice in a unifying vision. We focus on two specific student-led initiatives aimed at combatting hunger and homelessness in the St. Louis community as a way to illustrate the tension between structural and personal expressions of justice, as well as to highlight the important synergies that emerge when these complementary modalities are reconciled.